Circulating Serovars of Leptospirosis and Associated Factors in Jos, North Central Nigeria - George Yilzem Gurumyen; Theophilus Aghogho Jarikre; Polycarp Nwunuji Tanko; Olusegun Victor Taiwo; Elmina A. Abiayi; Derrick Adu Asare; Asinamai Athliamai Bitrus; Benjamin Obukowho Emikpe (Media Kedokteran Hewan, 2026)
Leptospirosis is an emerging, neglected and underreported zoonotic disease. With limited records of circulating Leptospira serovars in Nigeria. This study aimed to investigate Leptospira serovars and its associated factors in dogs in Jos, Plateau State, Nigeria. A total of 180 blood samples were collected from dogs presented to two veterinary facilities between January 2024 and March 2025. The samples were screened using the microscopic agglutination test (MAT) against eight Leptospira serovars. Data were analyzed using chi-square statistics to determine the associations between infection status and associated factors. Serovar Mini (34.4%) and Icterohaemorrhagiae (22.2%) had the highest seroprevalence rates among the sampled dogs. Mixed infections were common (45%), single-serovar infections were 20%, and 35% were negative. Age was significantly associated with infection (P< 0.001), with dogs aged ≤ 2 years showing the highest infection rate. Pyrexia was consistent in dogs infected with serovars Icterohaemorrhagiae and Mini serovars. To the best of our knowledge, this study provides the first serological evidence of Leptospira serovar Mini in dogs, whereas Icterohaemorrhagiae, Canicola, Grippotyphosa, Tarassovi, Bratislava, Pomona, and Hardjo continue to co-circulating in Nigeria. Hence, the need for genomic surveillance and the development of canine Leptospira vaccines to reflect circulating serovars in Nigeria.